fMRI in Non-human Primate: A Review on Factors That Can Affect Interpretation and Dynamic Causal Modeling Application - Jovellar, D. Blair; Doudet, Doris J. (Frontiers in Neuroscience, 2019)
Dynamic causal modelling (DCM)—a framework for inferring hidden neuronal states from brain activity measurements (e.g. fMRI) and their context-dependent modulation—was developed for human neuroimaging, and has not been optimized for non-human primate (NHP) studies, which are usually done under anesthesia. Animal neuroimaging studies offer the potential to improve effective connectivity modelling using DCM through combining functional imaging with invasive procedures such as in vivo optogenetic or electrical stimulation. Employing a Bayesian approach, model parameters are estimated based on prior knowledge of conditions that might be related to neural and BOLD dynamics (e.g., requires empirical knowledge about the range of plausible parameter values). As such, we address the following questions in this review: What factors need to be considered when applying DCM to NHP data? What differences in functional networks, cerebrovascular architecture and physiology exist between human and NHPs that are relevant for DCM application? How do anesthetics affect vascular physiology, BOLD contrast, and neural dynamics—particularly, effective communication within and between networks? Considering the factors that are relevant for DCM application to NHP neuroimaging, we propose a strategy for modelling effective connectivity under anesthesia using an integrated physiologic-stochastic DCM (IPS-DCM).